1991
DOI: 10.3109/00365529108998569
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Postoperative Paralytic Ileus with Cisapride

Abstract: The effect of cisapride on postoperative colonic motility was studied in 40 patients undergoing cholecystectomy under randomized, double-blind conditions. The patients received 10 mg of cisapride or placebo by intravenous injection starting on the day of surgery and repeated every 12 h until the 3rd postoperative day. The return of propagative motility in the colon was visualized by means of radiopaque markers and serial abdominal radiographs. Cisapride induced a significantly earlier return of propulsive moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…Cisapride is a 5-HT-4 agonist that facilitates acetylcholine release from the intrinsic plexus (Tonini, 1999). Several trials have shown that cisapride actually has a beneficial effect in shortening POI (Tollesson et al, 1991;Brown et al, 1999). In our study we found that cisapride stimulated phase II of the MMC in the duodenum and jejunum.…”
Section: Disscusionsupporting
confidence: 63%
“…Cisapride is a 5-HT-4 agonist that facilitates acetylcholine release from the intrinsic plexus (Tonini, 1999). Several trials have shown that cisapride actually has a beneficial effect in shortening POI (Tollesson et al, 1991;Brown et al, 1999). In our study we found that cisapride stimulated phase II of the MMC in the duodenum and jejunum.…”
Section: Disscusionsupporting
confidence: 63%
“…50, No. 12 CHEWING GUM REDUCING POSTOPERATIVE ILEUS that act on different parts of the gastrointestinal tract. 18,19,41,45 Chewing mimics food intake and stimulates the motility of human duodenum, 18 stomach, 19 and rectum.…”
Section: Discussionmentioning
confidence: 99%
“…The patients started chewing gum on Vol. 50,No. 12 CHEWING GUM REDUCING POSTOPERATIVE ILEUS the first postoperative day until first passage of flatus 22,25,26 or bowel motion.…”
Section: Characteristics Of Trialsmentioning
confidence: 96%
See 1 more Smart Citation
“…Cisapride, a 5-hydroxytryptamine agonist, is a gastrointestinal prokinetic drug devoid of antidopaminergic or direct cholinergic effects and without effects on mucosal epithelial se cretion [22], The drug stimulates motility along the digestive tract mainly by enhancing the release of acetylcholine from postgan glionic mesenteric nerve endings at gastroin testinal smooth muscle cells (myenteric plex us) [23,24], Cisapride has proven effective, e.g., in treatment of constipation resulting from disturbed intestinal motility without causing adverse central nervous system ef fects [25][26][27], Also, temporary gastrointesti nal paralysis after major abdominal surgery has been improved by cisapride treatment, especially by inducing an earlier return of prop agative motility in the ileum and colon [28].…”
Section: Discussionmentioning
confidence: 99%